NLRP3 Inflammasome Assembly in Neutrophils Is Supported by PAD4 and Promotes NETosis Under Sterile Conditions - Münzer, Patrick; Negro, Roberto; Fukui, Shoichi; di Meglio, Lucas; Aymonnier, Karen; Chu, Long; Cherpokova, Deya; Gutch, Sarah; Sorvillo, Nicoletta; Shi, Lai; Magupalli, Venkat Giri; Weber, Alexander N. R.; et al. (Frontiers in Immunology, 2021)
Neutrophil extracellular trap formation (NETosis) and the NLR family pyrin domain containing 3 (NLRP3) inflammasome assembly are associated with a similar spectrum of human disorders. While NETosis is known to be regulated by peptidylarginine deiminase 4 (PAD4), the role of the NLRP3 inflammasome in NETosis was not addressed. Here, we establish that under sterile conditions the cannonical NLRP3 inflammasome participates in NETosis. We show apoptosis-associated speck-like protein containing a CARD (ASC) speck assembly and caspase-1 cleavage in stimulated mouse neutrophils without LPS priming. PAD4 was needed for optimal NLRP3 inflammasome assembly by regulating NLRP3 and ASC protein levels post-transcriptionally. Genetic ablation of NLRP3 signaling resulted in impaired NET formation, because NLRP3 supported both nuclear envelope and plasma membrane rupture. Pharmacological inhibition of NLRP3 in either mouse or human neutrophils also diminished NETosis. Finally, NLRP3 deficiency resulted in a lower density of NETs in thrombi produced by a stenosis-induced mouse model of deep vein thrombosis. Altogether, our results indicate a PAD4-dependent formation of the NLRP3 inflammasome in neutrophils and implicate NLRP3 in NETosis under noninfectious conditions in vitro and in vivo.